Dry and wet spell analysis for crop planning in Chhattisgarh plain using Markov’s chain model - SINHA, B.L.; DEO, RAJENDRA KUMAR; SINHA, JITENDRA (Journal of Soil and Water Conservation, 2024)
Knowledge of sequences of dry and wet spells along with onset and withdrawal of rainy season is very important for successful agricultural crop planning and design of soil and water conservation measures. In the present study, Markov Chain probability model was applied to investigate the probable occurrences of dry and wet spells in Gariyaband district of Chhattisgarh plain using 30 years (1990 to 2020) rainfall data. The average annual rainfall of Gariyaband tehsil was found to be 1266.8 mm which was distributed erratically. Monsoon starts on the 25th standard meteorological week (SMW) and remains active up to 38th SMW. Initial, conditional and consecutive dry and wet week probabilities showed that a chance of occurrence of a week getting wet is high from 27th week onwards up to 35th week. Chances of occurrence of wet week of more than 30% at the beginning of Kharif season indicates that summer ploughing and initial seed bed preparations shall be taken up in the 24th–25th SMW and sowing operations can be taken up since 28th SMW. However higher values of CV showed that higher variability of rainfall during this period which questioned the success of growing of rainfed crops. In addition, harvesting excess runoff water for supplementary irrigation and construction of soil and water conservation measures need to be practiced between 29th–36th weeks for better rain water management.